2020
DOI: 10.3389/fmicb.2020.600221
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Vesicle Production as a Bacterial Defense Against Stress

Abstract: Membrane vesicles are the nano-sized vesicles originating from membranes. The production of membrane vesicles is a common feature among bacteria. Depending on the bacterial growth phase and environmental conditions, membrane vesicles show diverse characteristics. Various physiological and ecological roles have been attributed to membrane vesicles under both homeostatic and stressful conditions. Pathogens encounter several stressors during colonization in the hostile environment of host tissues. Nutrient defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 206 publications
(345 reference statements)
2
67
0
Order By: Relevance
“…In addition to rapid alteration in the phospholipids, Pseudomonads, like all Gram-negative bacteria, use vesiculation as a defence mechanism against various chemical (and non-chemical) stresses [34]. They release outer membrane vesicles (OMVs) with a diameter between 20 and 500 nm into the extracellular space, thereby altering the composition of the lipopolysaccharide (LPS) layer, the most distal part of their bacterial cell envelope.…”
Section: Built-in Cell Envelope Stress Response As Support Of Bioproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to rapid alteration in the phospholipids, Pseudomonads, like all Gram-negative bacteria, use vesiculation as a defence mechanism against various chemical (and non-chemical) stresses [34]. They release outer membrane vesicles (OMVs) with a diameter between 20 and 500 nm into the extracellular space, thereby altering the composition of the lipopolysaccharide (LPS) layer, the most distal part of their bacterial cell envelope.…”
Section: Built-in Cell Envelope Stress Response As Support Of Bioproductionmentioning
confidence: 99%
“…They release outer membrane vesicles (OMVs) with a diameter between 20 and 500 nm into the extracellular space, thereby altering the composition of the lipopolysaccharide (LPS) layer, the most distal part of their bacterial cell envelope. OMV formation and its numerous functions have been reviewed in detail [27,[34][35][36][37]. The fast release of OMVs plays a major role in stress response, leading to a more hydrophobic bacterial surface and thus enhancing biofilm formation [38].…”
Section: Built-in Cell Envelope Stress Response As Support Of Bioproductionmentioning
confidence: 99%
“…Membranes vesicles have been observed in D. alaskensis DSM16109, in cultures incubated in presence or absence of mitomycin C [93]. A previous study has suggested that after peptidoglycan lysis caused by endolysins, membrane vesicles can be formed from membranes [94]. Afterwards, in the present study we attempted to test cross infection among the three strains.…”
Section: Induction Of Desulfovibrio Prophagesmentioning
confidence: 76%
“…In addition, they have great potential in immunology and biotechnology applications. For these reasons in recent years, numerous studies have investigated and reviewed all the aspects of bacterial MVs, including their composition, functions, biogenesis mechanisms, immunomodulatory capacity, and potential applications (Mashburn-Warren and Whiteley, 2006;Schooling and Beveridge, 2006;Lee et al, 2008;Kaparakis-Liaskos and Ferrero, 2015;Schwechheimer and Kuehn, 2015;Jan, 2017;Mozaheb and Mingeot-Leclercq, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These new types of vesicles are also found to be secreted by pathogenic Gram-negative bacteria (Pérez-Cruz et al, 2015). Although the roles played by stress factors such as antibiotics and environmental growth conditions in promoting vesiculation in many bacteria are already known (Mozaheb and Mingeot-Leclercq, 2020), no stress factors have been identified that help to produce blebbing O-IMVs in S. vesiculosa M7 T .…”
Section: Introductionmentioning
confidence: 99%